2021
DOI: 10.3390/f12070897
|View full text |Cite
|
Sign up to set email alerts
|

Reed Canary Grass for Energy in Sweden: Yields, Land-Use Patterns, and Climatic Profile

Abstract: Research Highlights: (1) Reed canary grass (RCG) is analysed in Sweden compared to willow and poplar for 2001–2020. (2) Each crop presents a different land-use and climatic profile. (3) Average yield records of RCG are similar to willow and poplar. (4) There are divergences between trial-based and commercial yields. (5) Existing land-use change patterns suggest meadow > RCG and RCG > cereal. (6) RCG land area is very sensitive to policy incentives. Background and objectives: RCG is an alternative crop fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Several studies have used the IACS database in recent years, e.g., to classify and assess land use 56,57 and facilitate methodology development for the identification of crop types from satellite data 58,59 . For the purposes of this study, we collected and synthesized parcel-level data on crop cultivation for each reported field in Sweden for 18 years (2003 to 2020).…”
Section: Crop Data From Integrated Administrative and Control Systemmentioning
confidence: 99%
“…Several studies have used the IACS database in recent years, e.g., to classify and assess land use 56,57 and facilitate methodology development for the identification of crop types from satellite data 58,59 . For the purposes of this study, we collected and synthesized parcel-level data on crop cultivation for each reported field in Sweden for 18 years (2003 to 2020).…”
Section: Crop Data From Integrated Administrative and Control Systemmentioning
confidence: 99%
“…Mola-Yudego et al [18] compared the volume production, land-use patterns, and climatic profiles of reed canary grass versus traditional energy crops (i.e., poplars and willows) in Sweden. Reed canary grass is grown in colder climates in areas that have lower agricultural productivity than poplars and willows, yet they found its mean yields of 6 Mg ha −1 year −1 (experimental) and 3.5 Mg ha −1 year −1 (commercial) to be similar.…”
Section: Applications From Around the Globementioning
confidence: 99%
“…There are a total of 20 papers in the Special Issue representing 13 countries and four genera (Phalaris L., Populus L., Robinia L., Salix L.) (Figure 1; Table 1). In addition to the development and management of a Salix cultivar database [1], rural and urban applications represented in the Special Issue include: (a) forest buffers [2], (b) forest health screening [3,4], (c) phytoremediation [5][6][7], (d) short rotation coppice [8][9][10][11][12][13][14][15], (e) volume production [16][17][18], and (f) wastewater reuse [19,20] (Table 1). There were >130 genotypes from 27 genomic groups tested across all studies (Table 2), representing the importance of phyto-recurrent selection and other methods to choose clones for local and regional biomass production systems whose methodologies and approaches are relevant worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…Perennial grasses are considered promising energy crops due to a number of characteristics that make them particularly interesting for intensive biomass production compared to annual crops: high yield potential, high lignin and cellulose content in their biomass, high calorific value, low water content, and low complexity of field treatment. In addition, energy herbaceous crops can improve biodiversity conditions, provide opportunities for simultaneous phytoremediation and erosion control, increase soil organic carbon, and mediate water flow and nutrient content [1].…”
Section: Introductionmentioning
confidence: 99%